Experimental study on dynamic mechanical properties of concrete under sulfate attack - Liu, Ruixue; Mao, Xianbiao; Li, Bing; Li, Yan; Zhang, Lianying (Frontiers in Materials, 2025)
Research on the dynamic mechanical properties of concrete under sulfate attack is the basis for the reasonable design and performance evaluation of anti-explosion and impact resistance in concrete structures under the erosion environment. In this study, the mechanical properties of concrete specimens subjected to sulfate attack under impact compression were measured using the split Hopkinson pressure bar (SHPB) test system. The basic mechanical properties (stress-strain curve, compressive strength, elastic modulus, peak strain) of concrete specimens subject to sulfate attack under high strain rate were obtained, and the variation laws of macroscopic failure characteristics and characteristics of energy dissipation of concrete specimens subject to sulfate attack with the loading strain rate were summarized. The results show that the compressive strength and elastic modulus of concrete specimens under different sulfate concentrations exhibit a significant strain rate effect. As the strain rate increases, the compressive strength and elastic modulus of concrete specimens gradually increase; compared with concrete free from sulfate attack, the compressive strength and elastic modulus of concrete subject to sulfate attack are more significantly influenced by strain rate. Overall, the peak strain of concrete increases with the increase of strain rate, but when the strain rate increases to a certain extent, the peak strain changes little. Under the same sulfate concentration, the macroscopic failure degree of concrete specimens increases obviously with the increase of strain rate. The dissipation energy of concrete subject to sulfate attack is more sensitive to the strain rate compared with concrete free from sulfate attack, and the increase of strain rate will obviously decrease the energy utilization rate of concrete subject to sulfate attack.